Implementation of Integrated Marketing Communication at PT XYZ - Amborowati, Agustin; Hasibuan, Fauziah (International Journal of Sustainable Applied Sciences, 2023)
Intense competition in the economic sector forces every company and guides companies to always understand what is happening, what consumers want, and changes that exist so that every company, both developed and developing companies in this modern era, can still compete. This study aims to determine the implementation of Integrated Marketing Communication (IMC) at PT XYZ. The research design used is a case study that uses a descriptive qualitative approach by observing, analyzing data obtained from PT XYZ to conducting non-formal interviews with research subjects, then conducting descriptions or elaborations to draw conclusions. The results showed that the implementation of Integrated Marketing Communication (IMC) at PT XYZ was very effective, in the form of applying advertising, personal selling, direct marketing, sales promotion, public relations in marketing the products owned by PT XYZ. PT XYZ has implemented Integrated Marketing Communication (IMC), one of the elements implemented is Direct Marketing where salespeople make direct call offerings to offer PT XYZ products to customers.